FAKTOR-FAKTOR DETERMINAN PADA MOTIVASI KERJA GURU SEKOLAH DASAR - Laura F.N. Sudarnoto (Universitas Negeri Malang, 2016)
Abstract: The aim of this study is to describe the motivation of 121 teachers’ work at private Elementary School in Jakarta. The study of research objects as determinant factors include teachers’ commitment to school, the perception of leadership behaviors, and workplace conditions. Those variables are measured with assessment and behavior scale which the reliability is more than 0,90. Results of this study show that there is a positive and significant relationship of the three determinant factors toward the motivations of work, either individually or collectively. The effort that needs to be followed up is to maintain headmasters’ role as a leader because leadership is meaningful as a determinant factor that is important to increasing teachers’ motivation of work. Abstrak: Penelitian ini bertujuan untuk mendeskripsikan motivasi kerja 121 guru SD sekolah swasta di Jakarta. Kajian objek penelitian sebagai faktor determinan meliputi komitmen terhadap sekolah, persepsi terhadap perilaku kepemimpinan, dan kondisi tempat kerja. Variabel-variabel tersebut diukur dengan skala penilaian dan skala sikap yang memiliki reliabilitas masing-masing di atas 0,90. Hasil penelitian menunjukkan adanya hubungan yang positif dan signifikan dari ketiga faktor determinan terhadap motivasi kerja, baik secara sendiri-sendiri maupun bersama-sama. Usaha yang perlu ditindaklanjuti adalah mempertahankan peran kepala sekolah yang baik sebagai pimpinan karena kepemimpinan sangat bermakna sebagai faktor determinan yang penting untuk meningkatkan motivasi kerja para guru.